An exploratory case study of generative AI in supporting EFL students’ written communicative competence - Nur Arifah Drajati; Lynde Tan; Yulia Tria Hapsari (Universitas Muhammadiyah Purwokerto, 2026)
Generative Artificial Intelligence (GenAI) is rapidly transforming academic writing practices, raising concerns about its role in supporting the development of communicative competence. In English as a Foreign Language (EFL) contexts, where students often struggle to produce socially appropriate and contextually coherent texts, GenAI tools such as ChatGPT offer immediate linguistic support, model texts, and feedback. Despite the growing use of GenAI tools, limited classroom-based evidence exists on how GenAI supports EFL students’ written communicative competence in authentic tasks. This qualitative case study investigates the role of ChatGPT-5 in supporting EFL university students’ written communicative competence in an email-writing task and examines how teachers mediate AI-assisted learning. The study involved thirty-nine second-year Indonesian university students. Data were collected from students’ email drafts, semi-structured interviews, classroom observations, and learning artifacts, including screen captures and peer feedback. The findings indicate that students demonstrated development in sociolinguistic and discourse competence, particularly in refining tone, applying appropriate politeness strategies, and improving cohesion and coherence in their written texts. Even though ChatGPT played a role in these changes, but it was not the only thing that contributed. The results are affected by the combination of AI-generated input, teacher guidance, peer feedback, and students’ ability to think critically about the AI’s suggestions. This suggests that pedagogical mediation is very important for helping students develop their communicative competence when they use AI.